Serum GFAP as a biomarker for disease severity in multiple sclerosis - Abdelhak, A.; Huss, A.; Kassubek, J.; Tumani, H.; Otto, M. (Scientific reports, 2018)
While neurofilament light chain (NfL) measurement in serum is a well-established marker of neuroaxonal damage in multiple sclerosis (MS), data on astroglial markers in serum are missing. In our study, glial fibrillary acid protein (GFAP) and NfL were measured in cerebrospinal fluid (CSF) and serum of MS patients and patients with other non-inflammatory neurological diseases (OND) using the Simoa technology. Clinical data like age, gender, expanded disability status scale (EDSS) and MRI findings were correlated to neurochemical markers. We included 80 MS patients: 42 relapsing-remitting MS (RRMS), 38 progressive MS (PMS), as well as 20 OND. Serum GFAP levels were higher in PMS compared to RRMS and OND (p < 0.001, p = 0.02 respectively). Serum GFAP levels correlated with disease severity in the whole MS group and PMS (Spearman-rho = 0.5, p < 0.001 in both groups). Serum GFAP correlated with serum NfL in PMS patients (Spearman-rho = 0.4, p = 0.01). Levels of serum GFAP were higher with increasing MRI-lesion count (p = 0.01). in summary, we report elevated levels of GFAP in the serum of MS patients. Since serum levels of GFAP correlate with the clinical severity scores and MRI lesion count, especially in PMS patients, it might be a suitable disease progression marker.